Readiness of Human Resources in Management Joint Business Group - Kahar Kahar; Kiki Rasmala Sani; Mochamat Nurdin (Jurnal Ad'ministrare, 2021)
Poor Empowerment Program through Joint Business Groups or KUBE (Kelompok Usaha Bersama *in English: Joint Business Group). The form of this program is to provide Direct Social Empowerment Assistance or business capital for the poor to facilitate these community groups which have been accommodated in a group, namely KUBE to manage and develop Productive Economic Enterprises. This type of research is qualitative research using observation, interview, and documentation techniques as a data collection tool. While the data analysis technique is done by collecting data, reducing data, and drawing conclusions. The results of this study indicate that the community welfare improvement program is implemented through the establishment of KUBE and providing business capital assistance KUBE to build businesses and increase people's income; there is still a need for capacity building for managers so that the formed KUBE can become a sustainable business model. This research can be used as a reference in preparing human resources through joint business groups at the village level because previous research focused on the district/city level.